Piloting Test of a Mindfulness Meditation Intervention to Reduce Stress in Younger Stroke Patients - Zenebe Geneme; Anjali Perera; DaiWai M. Olson; Sonja E. Stutzman (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The population of younger people having strokes is growing. Persons who are younger and have a stroke have specific stressors after a stroke that those over 60 may not experience (e.g., ability to earn an income, provide for a family, returning to work, etc.). Aim. In order to address some of these age-specific stressors, new and novel approaches to stress mediation are needed. In order to address this gap in the literature this study piloted a mindfulness meditation with younger in hospital stroke survivors. Material and Methods. Prospective non-randomized pilot study of in-hospital stroke patients < 60 years of age. Baseline assessment included the Perceived Stress Scale (PSS), heart rate (HR), blood pressure (BP), and respiratory rate (RR). Patients received a 10-minute mindfulness training session with instructions for home use. PSS, HR, BP, and RR were collected immediately after training and telephone assessments of PSS were collected 30-day post discharge. Results. The mean age of the 21 patients included in the final analysis was 47.4 years. Paired t-test showed statistically significant differences in heart rate (p < 0.001) and respiratory rate (p < 0.001) before and after the intervention, but no statistically significant differences in pre and post training blood pressure (p = 0.480). There was no statistically significant difference in PSS scores before and after the training. Conclusions. The findings of this study suggest that the mindfulness intervention is feasible for in-hospital stroke patients and shows promise for reducing stress, as indicated by physiologic changes such as lowering heart and blood pressure rates. (JNNN 2019;8(2):48–53)